The Cognitive Impacts of Public Transport Dependency on Time Management Among Undergraduate Students in Lahore - Eshal Qaiser; Laiba Hamza; Hafiz Syed M. Yasir (Journal of Religion and Society, 2026)
The purpose of the research is to understand how commuting experiences contribute to mental exhaustion and disrupt students’ academic routines, while also exploring the relationship between public transport dependency, cognitive fatigue, and time management among undergraduates in Lahore. A quantitative descriptive research design was employed. The sample consisted of undergraduate students from public and private universities in Lahore who primarily relied on public transportation for commuting. Participants were selected through convenience sampling. Data was collected using a self-report questionnaire with Likert-scale items designed to measure transport dependency and commute characteristics. The study was guided by an integrated theoretical framework drawing upon stress–cognition models, Cognitive Load Theory, and self-regulation theory (Sweller et al., 2019; Vogel & Schwabe, 2019; Zimmerman, 2020). These frameworks propose that continuous exposure to environmental stressors and excessive cognitive demands leads to fatigue, reduced attentional control, and impaired self-regulatory capacities, including effective time management. Data were collected using a structured Google Form questionnaire and analyzed using IBM SPSS Statistics (Version 26). Descriptive statistics, including frequencies, percentages, means, and standard deviations, were used to analyze students’ responses. Cronbach’s alpha was computed using IBM SPSS Statistics (Version 26). Descriptive statistics summarized the data, while correlational and regression analyses examined the predictive relationships among the study variables. Findings revealed that public transport dependency and adverse commute characteristics significantly contribute to cognitive fatigue, which in turn negatively affects cognitive functioning and time management. The study recommends that educational institutions acknowledge commuting-related cognitive strain by implementing flexible academic policies and procedures. Furthermore, improvements in public transport efficiency and student-centered urban planning are recommended to support students’ cognitive well-being and academic success. Keywords: Cognitive fatigue, public transport dependency, self-regulation, time management, undergraduate students https://doi.org/10.5281/zenodo.18393952